Propolis-loaded liposomes: characterization and evaluation of the in vitro bioaccessibility of phenolic compounds - Saroglu, Oznur; Karadag, Ayse (IAPC PUBLISHING, 2024)
Background and purpose: Propolis has low water solubility, poor stability, and limited bioaccessibility of phenolic constituents when subjected to in vitro digestion. To overcome these drawbacks, the liposomal encapsulation method can be employed. Experimental approach: Soybean phosphatidylcholine lecithin mixed with Tween 80 (T80) and ammonium phosphatides (AMP) was used to produce propolis extract (PE)-loaded liposomes. The mean particle size, zeta potential, encapsulation efficiency values, and transmission electron microscopy analysis were used to characterize liposomes. Individual phenolics were determined for digested and nondigested propolis-loaded liposomes and propolis extract. Key results: Tween 80 incorporation reduced the size of unloaded liposomes, whereas AMP inclusion yielded larger liposomes. In both formulations, PE loading significantly increased the size and reduced the zeta potential values and homogeneity of the size distribution. In free PE, the most bioaccessible polyphenols were phenolic acids (3.20 to 5.63 %), and flavonoids such as caffeic acid phenethyl ester, galangin, pinobanksin, and pinocembrin (0.03 to 2.12 %) were the least bioaccessible. Both liposomal propolis provided significantly higher bioaccessibility of phenolic compounds. The liposomes with T80 and AMP in their compositions recovered 52.43 and 185.90 % of the total amount of phenolic compounds in the nondigested samples, respectively. The liposomes containing AMP not only exhibited high solubility for PE but also provided protection to the phenolic compounds during in vitro digestion. Conclusion: Liposomal encapsulation could be a promising approach to improving the solubility and stability of PE in digestive fluids, making it suitable for the delivery of propolis in oral formulations.
Keywords: Ammonium phosphatides; Tween 80; in vitro digestion; encapsulation; flavonoids; STABILITY; EXTRACT; MICROENCAPSULATION; MECHANISM; PH; Pharmacology & Pharmacy